Generalized Higher Left Centralizer of Prime Γ-Rings - salih, Salah Mehdi; Karim, Mazen O; Haetinger, Claus (JOURNAL OF ADVANCES IN MATHEMATICS, 2022)
In this paper we introduce the concepts of generalized higher left centralizer and generalized Jordan higher left centralizer of Γ-rings M as well as we proved that every generalized Jordan higher left centralizer of certain Γ-ring M is generalized higher left centralizer of M and we prove every Jordan generalized higher left centralizer of certain Γ-ring M is Jordan generalized triple higher left centralizer of M.